An Electronic Medical Record in Pediatric Medical Education: Survey of Medical Students' Expectations and Experiences - Cheng, Daryl R.; Scodellaro, Thomas; Uahwatanasakul, Wonie; South, Mike (Applied Clinical Informatics, 2018)
Objective This study sought to quantitatively characterize medical students' expectations and experiences of an electronic health record (EHR) system in a hospital setting, and to examine perceived and actual impacts on learning.Methods Medical students from July to December 2016 at a tertiary pediatric institution completed pre- and postrotation surveys evaluating their expectations and experience of using an EHR during a pediatric medicine rotation. Survey data included past technology experience, EHR accessibility, use of learning resources, and effect on learning outcomes and patient–clinician communication.Results Students generally reported high computer self-efficacy (4.16 ± 0.752, mean ± standard deviation), were comfortable with learning new software (4.08 ± 0.771), and expected the EHR to enhance their overall learning (4.074 ± 0.722). Students anticipated the EHR to be easy to learn, use, and operate, which was consistent with their experience (pre 3.86 vs. post 3.90, p = 0.56). Students did not expect nor experience that the EHR reduced their interaction, visual contact, or ability to build rapport with patients. The EHR did not meet expectations to facilitate learning around medication prescribing, placing orders, and utilizing online resources. Students found that the EHR marginally improved feedback surrounding clinical contributions to patient care from clinicians, although not to the expected levels (pre 3.50 vs. post 3.17, p < 0.01).Conclusion Medical students readily engaged with the EHR, recognized several advantages in clinical practice, and did not consider their ability to interact with patients was impaired. There was widespread consensus that the EHR enhanced their learning and clinician's feedback, but not to the degree they had expected.
Keywords: EHR; medical student; education; curriculum